Dynamics of the Koshi River on the Perspective of Morphology and Sedimentation with Emphasis on Post Disaster Impact of the 2008 Koshi Flood - Kafle, K.R.; Khanal, S.N.; Dahal, R.K. (Kathmandu University Journal of Science, Engineering and Technology, 2015)
The Koshi river is one of the most dynamic rivers in the world. It has shifted about 115 km westward due to sedimentation and tectonic activities during the past 200 years. Dynamic nature of the Koshi is revealed by its erosive nature and high capacity of carrying silt and sand from highlands. Disaster from floods are frequent in this river channel because of encroachment in watershed, high denudation rate, torrential rainfall in the upland as well as poor design of manmade structures along the river channel. The 2008 Koshi flood is one of the most catastrophic events in last decade. In this flood, millions of people are affected and lost their properties amounting to billion dollars. Most researches on Koshi flood disasters were concentrated on immediate effects that spanned about 1-2 years post flood period. Research works over last 50 years on Koshi revealed that the lowland Koshi basin, specially downstream from Chatara, has high flood disaster risk because of the poor maintenance and monitoring of the river training works done with poor understating of the dynamism of the river. Adversely, the disaster management was always ineffective, though the flood incidences were frequent since last 4 to 5 decades. The study on long term effect to health and long term effects of sedimentation on agricultural land in post flood disaster management phase are highly insufficient. Thus, for the lowland area of Koshi, adaptation strength and resilience on the future flood disasters need to be thoroughly investigated for the effective and efficient post disaster management.